Sex-Specific Differences in MicroRNA Expression During Human Fetal Lung Development - Lin, Nancy W.; Liu, Cuining; Yang, Ivana V.; Maier, Lisa A.; DeMeo, Dawn L.; Wood, Cheyret; Ye, Shuyu; Cruse, Margaret H.; Smith, Vong L.; Vyhlidal, Carrie A.; Kechris, Katerina; Sharma, Sunita (Frontiers in Genetics, 2022)
Background Sex-specific differences in fetal lung maturation have been well described; however, little is known about the sex-specific differences in microRNA (miRNA) expression during human lung development. Interestingly, many adult chronic lung diseases also demonstrate sex-specific differences in prevalence. The developmental origins of health and disease hypothesis suggests that these sex-specific differences in fetal lung development may influence disease susceptibility later in life. In this study, we performed miRNA sequencing on human fetal lung tissue samples to investigate differential expression of miRNAs between males and females in the pseudoglandular stage of lung development. We hypothesized that differences in miRNA expression are present between sexes in human lung development and may contribute to the sex-specific differences seen in pulmonary diseases later in life. Methods RNA was isolated from human fetal lung tissue samples for miRNA sequencing. The count of each miRNA was modeled by sex using negative binomial regression models in DESeq2 and adjusted for post-conception age, smoke exposure and batch effects. Then, miRNAs were screened for sex-specific age-trajectories using a likelihood ratio test to determine if miRNA expression levels by age were distinct between male and females. Results miRNA expression profiles were generated on 298 samples (166 males and 132 females). Of the 899 miRNAs expressed in human fetal lung tissue from the pseudoglandular stage of lung development, we identified 62 autosomal miRNAs that were significantly differentially expressed by sex after covariate adjustment. Estimated gestational age explained the largest variability in miRNA expression; 94 miRNAs had a sex-specific pattern of miRNA expression that were modified by age over the course of the pseudoglandular period. Conclusions Our study demonstrates differential expression of numerous autosomal miRNAs between the male and female developing human lung. Some of these differences in miRNA expression may impact susceptibility to pulmonary disease later in life. Additionally, the expression of some miRNAs are modified by age across the pseudoglandular stage in a sex-specific way. Our results suggest that sex-specific miRNA expression during human lung development may be a potential mechanism to explain sex-specific differences in lung development.